2015
DOI: 10.1186/s12947-015-0037-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of inpatient multimodal cardiac imaging appropriateness at large academic medical centers

Abstract: BackgroundResponding to concerns regarding the growth of cardiac testing, the American College of Cardiology Foundation (ACCF) published Appropriate Use Criteria (AUC) for various cardiac imaging modalities. Single modality cardiac imaging appropriateness has been reported but there have been no studies assessing the appropriateness of multiple imaging modalities in an inpatient environment.MethodsA retrospective study of the appropriateness of cardiac tests ordered by the inpatient General Internal Medicine (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…Having said this, we were able to classify all patients in this study using this method. Others have also reported very high classification rates approaching 100% based on similar methods . Third, the retrospective nature of the study and the associated chart review to determine appropriateness precluded the ability for our data abstracters to abstract data in a blinded manner.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Having said this, we were able to classify all patients in this study using this method. Others have also reported very high classification rates approaching 100% based on similar methods . Third, the retrospective nature of the study and the associated chart review to determine appropriateness precluded the ability for our data abstracters to abstract data in a blinded manner.…”
Section: Discussionmentioning
confidence: 98%
“…Bhatia and colleagues examined the appropriate use of inpatient cardiac noninvasive diagnostic testing, specifically transthoracic echocardiography (TTE), trans‐esophageal echocardiography (TEE), and single‐photon emission myocardial perfusion scanning (MPI) in a major university teaching center. They reported that, overall, 91% of tests were appropriate, 4% may be appropriate, and 5% were rarely appropriate . When broken down to constituent parts, 90% of TTEs were deemed to be appropriate, while 93% of single photon emission tomography (SPECT) were classified as appropriate as were 95% of TEEs.…”
Section: Discussionmentioning
confidence: 99%
“…There is a suggestion that clinical decision-making support tools can increase the relative proportion of several different imaging tests designated as appropriate, even within a year of implementation [20, 21]. This could also fulfill a role as an additional quality improvement measure, while helping to streamline utilization of noninvasive imaging techniques [22]. …”
Section: “Teaching” the Auc: Interventions Used To Improve The Applicmentioning
confidence: 99%
“…In the largest study to date, performed in 1812 patients from a single US academic center, 82% were appropriate, 12% were inappropriate, and 5% were uncertain. One in ten referrals at our center were considered inappropriate which is slightly higher than 2015 reports in the US (5%) and Canada (7%) but lower than those outside North America (15% to 20%) . In the US, compliance with the AUC is essential as requests for tests are only authorized if they comply with the radiology manager's precertification criteria which are in line with the AUC .…”
Section: Discussionmentioning
confidence: 86%
“…Prior revision of the 2007, AUC was prompted by several reports of unclassified studies which were clinically indicated and had an impact on patient management. However, data from centers outside the US suggest over 95% of TTEs can be classified by the 2011 AUC indicating these criteria could be applied overseas. Furthermore, a number of studies have found TTEs classified as appropriate have greater detection rates of new, unexpected, or treatable findings compared to inappropriate TTEs.…”
Section: Introductionmentioning
confidence: 99%